Investigating the Structural Behaviour of RC Ribbed Skew Slab by Changing Skew Angle in Feasible Range - M. S. Hora (Research and Developments in Engineering Research Vol. 2, 2023)
The analysis of skew slab is quite complicated than those of a conventional rectangular slab. This chapter looks at the parametric properties of RC un-stiffened and ribbed skew slabs (stiffened by rib beams) with skew angles ranging from 20° to 50° in 5° intervals. The analyses are performed on un-stiffened and ribbed skew slabs with two short edges that are simply supported and two long edges that are free. ANSYS software is used to create models for 14 cases of un-stiffened and ribbed skew slabs. The results are compared in terms of displacements, bending moments, twisting moments, von-Mises stress, bending stresses, and shear stresses. The value of maximum deflection in un-stiffened and ribbed skew slabs decreases significantly with increase in skew angle.